Improvement of Neurodegenerative Disease after Use of Vemurafenib in Refractory BRAF V600E-Mutated Langerhans Cell Histiocytosis: A Case Report - Young Kwon Koh; Su Hyun Yoon; Sung Han Kang; Hyery Kim; Ho Joon Im; Pyeong Hwa Kim; Ah Young Jung; Kyung-Nam Koh (The Korean Society of Pediatric Hematology-Oncology, 2022)
Langerhans cell histiocytosis (LCH) is a rare histiocytic disorder characterized by heterogenous lesions infiltrated with CD1a+/CD207+ cells. Although LCH has a relatively good prognosis, the prognosis for patients with LCH refractory to standard chemotherapy is poor. Neurodegenerative LCH (ND-LCH) is a central nervous system complication of LCH that is characterized by progressive radiological and clinical abnormalities. Symptomatic ND-LCH is difficult to treat and therefore has a poor prognosis. A two-year-old boy presented with a scalp mass. Biopsy confirmed LCH. Whole-body imaging revealed LCH involvement in multiple bones of the skull, facial bones, and lungs. Prednisolone and vinblastine chemotherapy was initiated. One-year post-treatment, most of the lesions in the bones and lung nodules disappeared, and chemotherapy was discontinued. New neurodegenerative lesions appeared 4 months after chemotherapy was discontinued. Second-line chemotherapy using cytarabine, vincristine, and prednisolone was initiated. However, neurological manifestations of ND-LCH worsened post second-line treatment, and the treatment was switched to cytarabine and cladribine. Despite third-line chemotherapy, the lesions progressed, and neurological deficits worsened. After identifying BRAF V600E mutation in the tumor tissue using next-generation sequencing, cytotoxic chemotherapy was discontinued and vemurafenib treatment was initiated. One-year post-vemurafenib therapy, ND-LCH manifestations regressed, and the patient experienced neurological improvement.